Procedural Fairness and Fear of Crime: Extending the Procedural Justice Theoretical Model Under the Chinese Context - Liu, Jianhong (Crime & delinquency, 2025)
This study examines the relationship between procedural fairness and fear of crime in the context of China. Based on original data collected from a random sample of 2,245 residents in a southeast city in China, this study reveals a salient influence of procedural fairness on fear of crime, reflected by its significant positive effects on not only emotional-based fear but also cognitive fear (perceived risk of victimization). Results also suggest that perceived neighborhood cohesion and police trustworthiness partially mediate the relationship between procedural fairness and the outcome variable. The findings of this study demonstrate broad consequences of procedural fairness (a meaningful social impact within the community) that go beyond its implications for legitimacy and compliance.